The Potential of Pop-Up Artworks for Visual Communication in Digital Media - Vanessa Yusuf (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
The pop-up mechanism or paper engineering is often referred to as a physical card or book, which can show 3D objects when it is opened. In fact, pop-up artworks can also be found in digital media such as movies, animation, video games, video advertisement, and music video. There are many interesting differences between physical pop-up and digital pop-up that can be analyzed to maximize its potential and create great visual effects, especially in digital media. This research uses a qualitative descriptive method by collecting data through observation of digital pop-up artworks and literature studies. Various examples will be analyzed to find out the strengths, weaknesses, and potential of pop-up artworks for visual communication in digital media.